The Role of Emotional and Aesthetic Factor of Perception in Making Customer Decisions - S. A. Afonskiy (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Due to the fact that the majority of goods and services are produced in the same technological environment, possess similar design and can hardly be distinguished by their technical characteristics and assessed by manufacturer and trade outlets in a similar way it becomes necessary to mention in trade offers certain non-price competitive advantages, i. e. to provide goods and services with brand – new emotional and aesthetic tint. Customer chooses the product using his/her feelings, emotions, mood, sympathy to the image, which is formed in according with metaphors, fixed images and cultural codes. It can be proved by our research (focus-group) that shows that 93 % of the audience rely on their feelings, mood and impressions in choosing goods, which can change even during the process of choosing and it can cancel preliminary plans and decisions. Percent ratio between mental and emotional decisions can differ depending on age, gender, character of customers, however today we cannot ignore emotional factor of customer perception in the process of market promotion of goods and services.